2008
DOI: 10.1002/pmic.200700564
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of plasma proteins that bind GlialCAM using ProteinChip™ Arrays, SELDI‐TOF MS, and nano‐LC MS/MS

Abstract: In order to fully understand biological processes it is essential to identify interactions in protein complexes. There are several techniques available to study this type of interactions, such as yeast two-hybrid screens, affinity chromatography, and coimmunoprecipitation. We propose a novel strategy to identify protein-protein interactions, comprised of first detecting the interactions using ProteinChips and SELDI-TOF MS, followed by the isolation of the interacting proteins through affinity beads and RP-HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…HepaCAM was recently demonstrated to be differentially expressed in human hepatocellular carcinoma [13,14]. Studies have shown that the expression of hepaCAM is frequently lost in human hepatocellular carcinoma and processed a tumor suppressor gene [7,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…HepaCAM was recently demonstrated to be differentially expressed in human hepatocellular carcinoma [13,14]. Studies have shown that the expression of hepaCAM is frequently lost in human hepatocellular carcinoma and processed a tumor suppressor gene [7,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Initially analysis of the integrity of CCL18 on the NP20 ProteinChip was first determined by applying CCL18 (5 μl at a concentration of 1 mg/ml) onto a NP20 ProteinChip Array (BioRad) as previously described (24). A saturated solution of sinapinic acid in 50% acetonitrile containing 1% Trifluoroacetic acid (TFA) in distilled H 2 O was added onto each spot and air-dried.…”
Section: Methodsmentioning
confidence: 99%
“…The affinity reagent may be a protein, antibody, peptide, aptamer or another biomolecule (Tuerk & MacDougal-Waugh, 1993;Durham & Regnier, 2006;Cole et al, 2007;Csanky et al, 2007;Sennels et al, 2007;Dubois et al, 2008;Evans-Nguyen et al, 2008;Favre-Kontula et al, 2008). Immuno-affinity chromatography of specific antibodies immobilized to hydrazide resin and monitored by mass spectrometry has been shown to be in the ng/mL range and shows agreement with ELISA (Nicol et al, 2008) and may be sensitive to femtomol amounts on column (Keshishian et al, 2007;Kulasingam et al, 2008).…”
Section: Affinity Chromatographymentioning
confidence: 95%